2012
DOI: 10.1177/0013164412442941
|View full text |Cite
|
Sign up to set email alerts
|

The Empirical Power and Type I Error Rates of the GBT and ω Indices in Detecting Answer Copying on Multiple-Choice Tests

Abstract: The generalized binomial test (GBT) and ω indices are the most recent methods suggested in the literature to detect answer copying behavior on multiple-choice tests. The ω index is one of the most studied indices, but there has not yet been a systematic simulation study for the GBT index. In addition, the effect of the ability levels of the examinees in answer copying pairs on the statistical properties of the GBT and ω indices have not been systematically addressed as yet. The current study simulated 500 answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…Random item copying procedure was applied for fixed copying amount of 40% for each replication. Amount of copying was taken and fixed as 40% for each condition because previous studies [23], [26] [30], [31] showed that power rates of indices were quite satisfactory for 30% and more.…”
Section: Research Methods 21 Research Designmentioning
confidence: 99%
See 4 more Smart Citations
“…Random item copying procedure was applied for fixed copying amount of 40% for each replication. Amount of copying was taken and fixed as 40% for each condition because previous studies [23], [26] [30], [31] showed that power rates of indices were quite satisfactory for 30% and more.…”
Section: Research Methods 21 Research Designmentioning
confidence: 99%
“…Ability levels of copier and source are important for the performance of answer-copying indices. Several studies in the literature have pointed to the importance of examinee ability levels on answer copying [26], [34]. For this study the abilities of examinees were obtained by using irtoys [35] R package depending on 2PL Item Response Model.…”
Section: Research Methods 21 Research Designmentioning
confidence: 99%
See 3 more Smart Citations